Amyloid‐β protein and MicroRNA‐384 in NCAM‐Labeled exosomes from peripheral blood are potential diagnostic markers for Alzheimer's disease. (26th April 2022) - Li, Ying; Meng, Shuang; Di, Wu; Xia, Ming; Dong, Lei; Zhao, Yue; Ling, Sihai; He, Jing; Xue, Xiaoxing; Chen, Xiali; Liu, Chengeng
Abstract: Objective: We aimed to establish a method to determine whether amyloid‐β (Aβ) protein and miR‐384 in peripheral blood neural cell adhesion molecule (NCAM)/ATP‐binding cassette transporter A1 (ABCA1) dual‐labeled exosomes may serve as diagnostic markers for the diagnosis of Alzheimer's disease (AD). Methods: This was a multicenter study using a two‐stage design. The subjects included 45 subjective cognitive decline (SCD) patients, 50 amnesic mild cognitive impairment (aMCI) patients, 40 AD patients, and 30 controls in the discovery stage. The results were validated in the verification stage in 47 SCD patients, 45 aMCI patients, 45 AD patients, and 30 controls. NCAM single‐labeled and NCAM/ABCA1 double‐labeled exosomes in the peripheral blood were captured and detected by immunoassay. Results: The Aβ42, Aβ42/40, Tau, P‐T181‐tau, and miR‐384 levels in NCAM single‐labeled and NCAM/ABCA1 double‐labeled exosomes of the aMCI and AD groups were significantly higher than those of the SCD, control, and vascular dementia (VaD) groups (all p < 0.05). The Aβ42 and miR‐384 levels in NCAM/ABCA1 dual‐labeled exosomes of the aMCI and AD groups were higher than those of the control and VaD groups (all p < 0.05). The exosomal Aβ42, Aβ42/40, Tau, P‐T181‐tau, and miR‐384 levels in peripheral blood were correlated with those in cerebrospinal fluid (all p < 0.05). Conclusion: This study, for the first time, established a method that sorts specific surface marker exosomes using a two‐step immune capture technology. The plasma NCAM/ABCA1 dual‐labeled exosomal Aβ42/40 and miR‐384 had potential advantages in the diagnosis of SCD. Abstract : In this study, we applied a newly developed technology to capture peripheral blood exosomes with both NCAM and ABCA1 protein tags. We found that Aβ42 and miR‐384 in these exosomes have great potential value for the diagnosis of SCD and aMCI.